THE GEOSPACE COMPETENCES WITH THE TPACK MODEL AND OUTDOOR EDUCATION - Isabel Maria GOMEZ- TRIGUEROS (European Journal of Geography, 2019)
The acquisition of geospatial competences is a priority in the initial training of teachers. This Nlearning must be achieved through two complementary pillars: technological tools, properly implemented, and the experiential referent of Outdoors Education. The main objective of this study was to evaluate the achievement of spatial and digital competences through an intervention in the classroom of Primary School Teachers of the University of Alicante, with the TPACK teaching model. For this, a mixed methodology has been used, based on the experience of the participants and the answers obtained in the Likert scale questionnaires. The results show significant conclusions about the positive value of the intervention for the achievement of such competences (geospatial and digital) as well as the convenience of implementing similar strategies in the training of future teachers.